Simulated hemodynamics in human carotid bifurcation based on Doppler ultrasound data - Luísa Costa Sousa (2014)
Background: Atherosclerotic lesions commonly develop at arterial branch sites. Noninvasive carotid artery ultrasound is a well-established and effective method which allows real-time images and measurements of flow velocities. We aimed to develop a methodology for patient-specific computational 3D reconstruction and blood flow simulation based on ultrasound image data. Material and Methods: Subject-specific studies based on the acquisition of a set of longitudinal and sequential cross-sectional ultrasound images and Doppler velocity measurements at common carotid artery (CCA) bifurcation were performed at a university hospital. A developed simulation code of blood flow by the finite element method (FEM) that includes an adequate structured meshing of the common carotid artery bifurcation was used to investigate local flow biomechanics. Results: Hemodynamic simulations of CCA bifurcations for six individuals were analysed. Comparing pairs (Doppler, FEM) of velocity values, Lin's concordance correlation coefficient analysis demonstrated an almost perfect strength of agreement (c = 0.9911), in patients with different degrees of internal carotid artery (ICA) stenosis. Numerical simulations were able to capture areas of low wall shear stress correlated with stagnation zones. Conclusions: Simulated hemodynamic parameters can reproduce the disturbed flow conditions at the bifurcation of CCA and proximal ICA, which play an important role in the development of local atherosclerotic plaques. This novel technology might help to understand the relationship between hemodynamic environment and carotid wall lesions, and have a future impact in carotid stenosis diagnosis and management.